Gator a-go-go - Dorsey, Tim (Dorsey, Tim. Serge Storms, 2010)
After a Miami crime gang ruins his spring break by targeting a snitch's son, drug-addled Serge A. Storms and his equally bloodthirsty deputy, Coleman, aim to track down the gang members and take them out.